Жанрово-изобразительные особенности сонетистики У. Шекспира и специфика их воспроизведения в восточнославянской поэзии - Хорсун, Ирина Александровна; Khorsun, Yrina (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статья посвящена исследованию жанрово-изобразительных особенностей сонетистики У. Шекспира и специфике их воспроизведения в восточнославянской поэзии. Сонетный цикл У. Шекспира – один из высочайших узоров западноевропейской поэзии XVI–XVII вв. Переводы шекспировских сонетов выполнены на многие языки мира, в том числе и на восточнославянские. Однако сопоставление их в жанрово-изобразительном аспекте еще не проводилось. Статья опирается на исследования, проводимые Г. Кочуром, Р. Нижегородцевым, а также на переводы, выполненные украинскими, белорусскими и русскими перевод-чиками. Проанализировав хронологию появления переводов сонетов У. Шекспира в украинской, белорусской и русской литературах, а также сравнив их варианты, приходим к выводу, что переводчики не обходились без внесения в сонет У. Шекспира элементов выявления своего, индивидуально-авторского видения. Переводы сонетов У. Шекспира на восточнославянские языки – яркая страница восприятия наследия классика в иноязычной среде.The article is devoted to the genre and visual features of Shakespeare’s sonnets and the specificity of their reproduction in the East Slavic poetry. Shakespeare’ssonnet cycle is one of the highest patterns of West European poetry of the XVI–XVII centuries.Shakespeare’s sonnets have been translated into many languages, including the East Slavic languages. However, they have not been compared in their genre and visual aspect yet. The article is based on the research carried out by G. Kochur, R. Nizhegorodtsev, as well as on the translations done by the Ukrainian, Belarusian and Russian translators. Having analyzed the chronology of the emergence of Shakespeare’s sonnets translation in Ukrainian, Belarusian and Russian literature, as well as having compared their variants, the author concludes that the translators did not do without giving their individual elements totheir translations of Shakespeare’s sonnets.The translations of Shakespeare’s sonnets into the East Slavic languagesare a bright page in the perception of classical heritage in a foreign language environment.
Genre and Visual Features of Shakespeare’s Sonnets and Specificity of their Reproduction in the East Slavic Poetry
Keywords: сонетистика; перевод; форма; содержание; русская поэзия; украинская поэзия; белорусская поэзия; sonnets; translation; form; content; Russian poetry; Ukrainian poetry; Belarusian poetry